2019
DOI: 10.3892/or.2019.6982
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of sonic Hedgehog signaling and histone deacetylase is an effective treatment for liver cancer

Abstract: Clinical trials have revealed that inhibition of sonic Hedgehog (SHH) signaling or histone deacetylase (HDAC) holds promise as a treatment for liver cancer. Based on our previous results, it was hypothesized that dual inhibition of SHH and HDAC may contribute to more efficient targeting of this disease. The effect of SHH inhibitor vismodegib as a single-agent or in combination with HDAC inhibitor entinostat was evaluated by Cell Counting Kit-8 (CCK-8) and flow cytometric assays, as well as immunoblotting. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Recently, microRNAs have been identified that they serve as signalling modulators in development of cancer, and play key roles in HCC cell progression [34] . Previous studies indicated that Wnt and Hh signalling plays key role during liver cancer cell development, migration, proliferation, and metastasis [22][23][24][25][26][27][28] . However, the molecular relationship between Wnt and Hh signalling in HCC to control cancer cell activity remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, microRNAs have been identified that they serve as signalling modulators in development of cancer, and play key roles in HCC cell progression [34] . Previous studies indicated that Wnt and Hh signalling plays key role during liver cancer cell development, migration, proliferation, and metastasis [22][23][24][25][26][27][28] . However, the molecular relationship between Wnt and Hh signalling in HCC to control cancer cell activity remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Gli1 activates a gel-forming mucin, MUC5AC expressions, which in turn inhibit E-cadherin-dependent cell-cell adhesions while activating pancreatic ductal adenocarcinoma cell migration and invasion [14] . Previous studies reported that the inhibitors of Hh signalling pathway suppressed liver cancer cell proliferation and invasion [22] ; inhibition of sonic Hh signalling together with histone deacetylase effectively control liver cancer [23] . Activation of Wnt/ β-catenin and macrophage was observed as key steps of liver cancer development [24] .…”
mentioning
confidence: 98%
“…Previous studies have reported that vismodegib induces apoptosis in several kinds of cancers (7,8,16) including PC (7). However, it is not clear whether induction of apoptosis occurs by an intrinsic or extrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SHH is relatively static in adult mammalian tissues, and abnormal activation of SHH signaling is associated with the occurrence and development of a variety of tumors, such as skin, 31 liver, 32 breast, 33 and lung cancer. 34 The involvement of SHH signaling in the occurrence of colon cancer may be related to the high expression of ALKAL1, which is indirectly involved in the invasion and metastasis of colon cancer.…”
Section: Discussionmentioning
confidence: 99%